HUMAN CAPITAL BENCHMARKING ON THE SUBJECT OF JUSTIFICATION OF REFLECTION IN THE ACCOUNTING SYSTEM AND REPORTING - Кундря-Висоцька, Оксана (Socio-economic relations in the digital society, 2020)
The article substantiates the problem of reflecting human capital as a separate object in the system of accounting and reporting. Human capital is not the property of the enterprise and is in temporary use for the duration of the employment contract. It proves that the non-accounting of such an object is a serious gap in accounting practice, which requires the development of the necessary methodological conditions for the identification, accounting and reporting of such categories as human resources, human capital. It offers a detailed study in the context of benchmarking effective practices of valuation, accounting and analysis of human capital in order to implement the acquired, proven experience in the light of morality, business and standards. The article substantiates the main provisions of the theory of human capital by analyzing the developed theories of both domestic and foreign scientists, based on which the key conditions for the identification, accounting and evaluation of human capital, human resources. It outlines the need to form a new accounting methodology that can objectively assess and take into account all the resources of the enterprise that can be used to make a profit. The research is based on two basic approaches to accounting and evaluation of human resources: the asset model and the utility model. In this regard, the article analyzes the current practices of companies, where the problem of human resources assessment is tested and offers the experience of sports, in particular, football companies, in which the cost of acquiring athletes is capitalized and reflected in non-current intangible assets. Based on the research, the article outlines the prospects for improving the informativeness of data on human resources / capital in accounting (financial) and management reporting.